Most northerly observation of a grizzly bear (ursus arctos) in Canada: photographic and DNA evidence from Melville Island, Northwest Territories - Doupe, Jonathan P.; England, John H.; Furze, Mark F.A.; Paetkau, D. (My University, 2007)
During geological studies in 2003 and 2004 on Melville Island, Northwest Territories, Canada, field parties photographed and gathered genetic information on one or more grizzly bears (Ursus arctos). To our knowledge, these data constitute the most northerly observations made of this species in North America. The DNA of a hair sample collected on Melville Island in 2004 is genetically indistinguishable from DNA collected from a population of grizzly bears around Paulatuk, Northwest Territories, along the northern mainland coast. It is also distinct from the DNA of the Viscount Melville polar bear (Ursus maritimus) population. Our evidence and review suggest that, at a minimum, transient grizzly bears are now regular visitors to the Canadian Arctic Archipelago. More research will be required to understand the significance of these observations, but a small viable population of grizzly bears may now be using areas in or around Melville Island.
Keywords: grizzly bear; High Arctic; hybrid; Melville Island; microsatellite analysis; Northwest Territories; Paulatuk; polar bear; Ursus arctos; Viscount Melville Sound